Development and Testing of a Modified Version of the Brief Pain Inventory for Use in Residential Aged Care Facilities - Auret, K.; Toye, Christine; Goucke, R.; Kristjanson, Linda; Bruce, D.; Schug, S. (Wiley-Blackwell Publishing, Inc., 2008)
OBJECTIVES: A two-phase study was conducted to refine a version of Cleeland's Brief Pain Inventory (BPI, Short Form) for use in residential aged care facilities (RACFs). DESIGN: The Australian Pain Society modified Cleeland's BPI by changing numerical response options to word descriptors. In Phase I, this version was tested in RACFs to determine the feasibility of its use, its stability over time, and its internal consistency reliability. Minor modifications resulted. In Phase II, the refined version was abbreviated, and the internal consistency reliability of this Modified Residents' Verbal BPI was examined. SETTING: RACFs. PARTICIPANTS: Thirty-three residents of RACFs in Phase I, 149 in Phase II. INTERVENTION: The study revised and abbreviated the BPI to better fit it for use in RACFs, examining the reliability of the tool. MEASUREMENTS: Mini-Mental State Examination, Global Deterioration Scale, modified BPI. RESULTS: The abbreviated tool comprises three items assessing pain intensity and three assessing pain interference. It also includes an item to specify pain location and a movement protocol. Cronbach alpha coefficient for six intensity and interference items was 0.72 (N=106). CONCLUSION: This abbreviated tool requires further testing but has demonstrated adequate internal consistency reliability and is a brief, multidimensional tool that appears feasible for assessing pain in RACFs, including use with residents who have some cognitive impairment. It shows promise as a screening tool and may be useful to assess the effectiveness of pain relief interventions and to measure pain prevalence.